2023
DOI: 10.7759/cureus.38886
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Fertility Outcomes Following Combined Clomiphene and Letrozole Versus Letrozole Therapy for the Treatment of Polycystic Ovarian Syndrome Subfertility

Abstract: Background: Poly Cystic Ovarian Syndrome (PCOS) affects 8-13% of women in their reproductive age and is one of the foremost causes of female subfertility. Traditionally, clomiphene citrate has been the first-line treatment for ovulation induction in PCOS. However, the European Society of Human Reproduction and Embryology (ESHRE) international evidence-based guidelines in 2018 recommended the use of letrozole as first-line therapy for ovulation induction in anovulatory PCOS women, due to better pregn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…By adjusting the patient's diet and developing personalized nutritional interventions, clinicians may, therefore, help patients to reduce weight while minimizing adverse reactions caused by the medication. 17,19 The results of our study showed that glucose metabolism indicators of patients in both groups after the treatment were lower than before the treatment, and significantly lower in patients who received TCM dietary support compared to the control group. This indicates that TCM nutritional therapy can significantly improve the glucose metabolism level of overweight PCOS patients.…”
Section: This Study Compares the Clinical Efficacy Of Tcm Nutritional...mentioning
confidence: 63%
See 2 more Smart Citations
“…By adjusting the patient's diet and developing personalized nutritional interventions, clinicians may, therefore, help patients to reduce weight while minimizing adverse reactions caused by the medication. 17,19 The results of our study showed that glucose metabolism indicators of patients in both groups after the treatment were lower than before the treatment, and significantly lower in patients who received TCM dietary support compared to the control group. This indicates that TCM nutritional therapy can significantly improve the glucose metabolism level of overweight PCOS patients.…”
Section: This Study Compares the Clinical Efficacy Of Tcm Nutritional...mentioning
confidence: 63%
“… 16 Body weight reduction was reported to restore physical health and reproductive function of PCOS patients. 15 , 17 For instance, Zhang et al 18 showed that weight loss of 6% -7% can restore normal ovulation in some PCOS patients. These studies further strengthening the notion that timely metformin treatment may be beneficial in overweight PCOS patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation